Status and associated factors of psychological resilience of Chinese medical aid team members under public health emergencies in a cross-sectional study - Xueyi Wei; Yinhua Liang; Jun Huang (PLoS ONE, 2025)
Background Chinese medical aid team members (CMATMs) play an important role in the implementation of China’s foreign health aid strategy. However, there is no research on the status and influencing factors of their psychological resilience. Objective This study aims to investigate the current status and influencing factors of psychological resilience of CMATMs. Methods From 3rd December, 2024–25th December, 2024, a convenience sampling method was used. Demographic information questionnaire, Connor Davidson Resilience Scale, General Self-Efficacy Scale, Self-Rating Anxiety Scale and Self-Rating Depression Scale were used to measure the psychological status of aid members. The influencing factors of psychological resilience were investigated through T-test, ANOVA, pearson correlation analysis, Kruskal-Wallis test and multiple linear regression. Results A total of 89 questionnaires were analysed. The total score of psychological resilience was 72.53 ± 13.48, which was generally at a good level. Pearson correlation analysis showed that self-efficacy was positively correlated with psychological resilience, while anxiety and depression were negatively correlated with psychological resilience. Multiple linear regression analysis revealed that factors related to psychological resilience included professional title(B = 4.679, P = 0.001), loneliness(B = 4.973, P = 0.000), classification of hardship areas in recipient countries(B = 1.864, P = 0.004), family support(B = 3.110, P = 0.001), cultural and entertainment(B = 3.537, P = 0.001), and direct participation in public health emergency response missions in recipient countries(B = −3.775, P = 0.006). Conclusions In the context of public health emergencies, CMATMs are prone to great pressure, which has a negative impact on their psychological resilience. This study provides a theoretical basis for formulating psychological intervention measures for CMATMs. Policymakers or healthcare administrators should regular assess CMATMs ‘ mental health status, strengthen mental health training, mobilize family and social support networks, improve infrastructure and welfare security policies to help them establish a more adaptive defense mechanism and maintain good psychological resilience during foreign aid.